Factors Influencing Maternal Health Literacy in Postpartum Women - Sangdang A; Phahuwatanakorn W; Limruangrong P (International Journal of Women's Health)
Alita Sangdang,1 Wanna Phahuwatanakorn,2 Piyanun Limruangrong2 1Master of Nursing Science Program in Midwifery, Faculty of Nursing, Mahidol University, Nakhonpathom, Thailand; 2Department of Obstetrics and Gynaecology Nursing, Faculty of Nursing, Mahidol University, Bangkok, ThailandCorrespondence: Wanna Phahuwatanakorn, Department of Obstetrics and Gynaecology Nursing, Faculty of Nursing, Mahidol University, 2 Wang Lang Road, Siriraj, Bangkoknoi, Bangkok, 10700, Thailand, Tel +66 2419 7466 80 ext. 1805, Fax +6624128415, Email wanna.pha@mahidol.ac.thBackground and Purpose: Maternal health literacy affects maternal and child health outcomes. The findings of previous studies have shown, that mothers with low maternal health literacy have inappropriate healthcare behaviors, especially among postpartum women. However, there is still a paucity of studies on the correlates of maternal health literacy in postpartum mothers. This study aimed to examine the predictive power of age, education level, family income, social support, and media use on maternal health literacy in postpartum women.Patients and Methods: A cross-sectional study was conducted among eligible postpartum women who delivered at full term and were admitted to the postpartum unit at two university hospitals. The purposive sampling method was employed. Data were initially collected at the postpartum unit. Then, after six weeks, data collection was performed online. The instruments used included the personal record form, the Social Support in Postpartum Questionnaire, the Media Use Questionnaire, and the Maternal Health Literacy Scale. After six weeks, nine women had not responded to the questionnaire at 6 weeks postpartum, and after identifying the outliers, 112 postpartum women were selected for analysis. Descriptive statistics and Multiple Linear Regression were used for data analysis in PASW Statistics version 18.Results: Age, education level, family income, social support, and media use together statistically significantly predicted maternal health literacy among postpartum mothers, accounting for 32.90% (R2 = 0.329, F = 10.382, p < 0.001). Specifically, social support (β = 0.545, p < 0.001) and family income (β = 0.174, p < 0.05) were statistically significant predictors of maternal health literacy.Conclusion: Postpartum mothers should be supported in their efforts to access maternal health information with the assistance of family members to promote maternal health literacy.Keywords: maternal health literacy, postpartum period, social support